2005
DOI: 10.1007/s11089-005-2337-z
|View full text |Cite
|
Sign up to set email alerts
|

Precipitants of Elderly Psychiatric Patient Assaults on Staff: Preliminary Empirical Inquiry

Abstract: Although there have been several studies of the characteristics of psychiatric patient assailants, there have been only six comprehensive, empirical assessments of precipitants to these assaults and no precipitant study has focused solely on elderly psychiatric patient assailants. This one and one-half year, retrospective study continued the inquiry into the nature of patient assault precipitants and focused only on elderly assailants. Older, male patients with a diagnosis of schizophrenia and histories of vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The National Audit of Violence (Royal College of Psychiatrists' Centre for Quality Improvement 2008) has demonstrated that nursing staff are more likely to be the victims of assaultive behaviour on in-patient units than are other clinical or nonclinical staff (64% v. 20% v. 23%). Other studies have observed assaults to occur most frequently during the day shift (Astrom 2002;Flannery 2005).…”
Section: Who Are the Potential Victims?mentioning
confidence: 89%
See 4 more Smart Citations
“…The National Audit of Violence (Royal College of Psychiatrists' Centre for Quality Improvement 2008) has demonstrated that nursing staff are more likely to be the victims of assaultive behaviour on in-patient units than are other clinical or nonclinical staff (64% v. 20% v. 23%). Other studies have observed assaults to occur most frequently during the day shift (Astrom 2002;Flannery 2005).…”
Section: Who Are the Potential Victims?mentioning
confidence: 89%
“…The first is a younger group, either male or female, with a history of schizophrenia, substance misuse or personality disorder. The second is an older population, with a history of organic disorder or psychosis (Flannery 2005).…”
Section: Articlementioning
confidence: 99%
See 3 more Smart Citations